What can we learn from China's health system reform?. (19th June 2019) - Meng, Qingyue; Mills, Anne; Wang, Longde; Han, Qide
Abstract : Qingyue Meng and colleagues assess what China's health system reform has achieved and what needs to be done over the next decade